2004
DOI: 10.1385/bter:98:3:219
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Superoxide Dismutase Activity in Obese Children

Abstract: The aim of the study was to evaluate the antioxidative Cu/Zn-SOD (superoxide dismutase) response to obesity-related stress in obese children compared to a similar-aged control group. Forty-eight exogenic obese children and 11 healthy children were compared for red cell Cu/Zn-SOD, glucose, and lipid profiles and the relations between them were investigated. Antioxidant response as Cu/Zn-SOD was significantly higher in the obese group (p<0.05). Although glucose and lipid levels were statistically higher in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 20 publications
5
22
0
1
Order By: Relevance
“…More recently, this same group documented the presence of protein oxidation in obese children, and suggested that insulin resistance may play an important role as a source of oxidative stress in the development of other diseases later in life (23 ). Erdeve et al have also shown the induction of oxidative stress in obesity and related antioxidative response, even in the pediatric age group (24 ). In a previous study, we also showed higher values of MDA, and an increased susceptibility of LDL-C to oxidation, in children with high family risk for premature CHD (5 ).…”
Section: Discussionsupporting
confidence: 76%
“…More recently, this same group documented the presence of protein oxidation in obese children, and suggested that insulin resistance may play an important role as a source of oxidative stress in the development of other diseases later in life (23 ). Erdeve et al have also shown the induction of oxidative stress in obesity and related antioxidative response, even in the pediatric age group (24 ). In a previous study, we also showed higher values of MDA, and an increased susceptibility of LDL-C to oxidation, in children with high family risk for premature CHD (5 ).…”
Section: Discussionsupporting
confidence: 76%
“…Besides AOPP, oxidation of plasma thiol groups, termed thiol stress [11], and located largely on albumin [24], is quantitatively the major manifestation of protein oxidation [12]. It was recently shown that stress oxidative markers in plasma increased significantly in children with obesity [2,8,20] but AOPP levels in obesity and insulin resistance had not been studied before. Obesity and type 2 diabetes are globally increasing health problems for young people, with significant individual and public health ramifications with respect to associated morbidity and mortality [7,22,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of diet with n-3 acids could -by reducing plasma triglyceride levels -alleviate insulin resistance, hypertension, and dyslipidemia, in the course of obesity-related metabolic syndrome (Lorente-Cebrián et al, 2013). On the other hand, an adequate intake of antioxidants naturally present in food can reduce oxidative damage associated with obesity, dangerous especially in co-existing hyperglycemia and hyperlipidemia (Erdeve et al, 2004).…”
Section: Discussionmentioning
confidence: 99%